P92 Thrombectomy in ischemic stroke patients with extended lesion and time window. (29th August 2022) - Broocks, G; Hanning, U; Bechstein, M; Kemmling, A; Fiehler, J; Meyer, L
Abstract : Introduction: Only limited data is available about a potential benefit of endovascular treatment (EVT) in patients presenting in the extended time window who also show signs of extensive infarction. Aim of study: To assess the effect of recanalization on functional outcome for patients in the extended time and lesion window. Methods: This multicenter observational study investigates the effect of recanalization after EVT, defined as mTICI≥2b, on functional outcome in anterior circulation ischemic stroke patients from the German Stroke Registry with an ASPECTS of 0–5 and time window between 6–24 hours who underwent CT and EVT.Primary endpoint was favorable outcome at day-90 (mRS≤3). The association of recanalization and outcome was assessed using logistic regression and inverse-probability weighting (IPW) analysis. Results: Out of 5853 patients, 285 (4.9%) met the inclusion criteria and were analyzed. 79 (27.7%) evidenced a favorable outcome at day 90. The rate of successful recanalization was 76% and was independently associated with higher probability of favorable outcome (aOR:4.39, 95%CI:1.79–10.72, p<0.0001). In IPW analysis, mTICI 2b/3 was associated with an 18.9% increase (95%CI:8.9–29.0%, p<0.0001) in probability for favorable outcome. Multivariable logistic regression analysis suggested a significant treatment benefit in a time window of 17.6 hours and ASPECTS 3–5. Conclusion: Vessel recanalization in patients with low ASPECTS and extended time window was associated with better functional outcomes in a time window up to 17.6h and ASPECTS of 3–5. The results of this study encourage current randomized trials investigating treatment of patients in the extended stroke lesion and time window. References: Nogueira RG, Jadhav AP, Haussen DC, et al . Thrombectomy 6 to 24 hours after stroke with a mismatch between deficit and infarct. N Engl J Med. 2018;378 (1):11–21. Kaesmacher J, Chaloulos-Iakovidis P, Panos L, et al . Mechanical thrombectomy in ischemic stroke patients with alberta stroke program early computed tomography score 0–5. Stroke 2019;50 (4):880–888. Almallouhi E, Al Kasab S, Hubbard Z, et al . Outcomes of mechanical thrombectomy for patients with stroke presenting with low alberta stroke program early computed tomography score in the early and extended window. JAMA Netw Open 2021;4 (12):E2137708. Do you have any conflict of interest to declare? : No